Peripheral-Type Benzodiazepine Receptor Antagonist Is Effective in Relieving Neuropathic Pain in Mice - Daisuke Kondo; Hironao Saegusa; Ritsuko Yabe; Ichiro Takasaki; Takashi Kurihara; Shuqin Zong; Tsutomu Tanabe (Elsevier, 2009)
Abstract.: cDNA microarray analysis showed the expression of peripheral-type benzodiazepine receptor (PBR) mRNA is slightly enhanced in the spinal cord of mice with spinal nerve injury (SNL) as compared with sham-operated mice. PBR transports cholesterol to the mitochondria, where cholesterol is converted to pregnenolone. Pregnenolone is then metabolized to progesterone, an activator of progesterone receptor, and further metabolized to produce allopregnanolone and 3α,21-dihydroxy-5α-pregnan-20-one (3α,5α-THDOC), positive allosteric modulators and activators of the GABAA receptor. In the present study, we first tested whether the enhanced PBR expression is causally related to neuropathic pain, and we found that the PBR antagonist PK11195 is effective in reducing SNL-induced mechanical allodynia and thermal hyperalgesia. Next we tested whether the PK11195-induced antinociception is attributable to reduced neurosteroid synthesis, which may possibly lead to reduced activation of the progesterone receptor and/or GABAA receptor. We found that allopregnanolone and 3α,5α-THDOC are effective in reducing the anti-hyperalgesic effect of PK11195, suggesting a partial contribution of reduced GABAA-receptor activation to PK11195-induced antinociception. Keywords:: peripheral-type benzodiazepine receptor, spinal nerve injury, neuropathic pain, PK11195, GABAA receptor